IMAGE-BASED VIRTUAL REALITY STRESS THERAPY APPLICATION (VRT-stressNOmore): AN ALTERNATIVE TOOL FOR SELF THERAPY - Nadia Diyana Mohd Muhaiyuddin; Ariffin Abdul Mutalib; Sobihatun Nur Abdul Salam; Norzaliza Alis (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Students in university are experiencing increased stress levels due to their daily routines. Students can self-manage their everyday stress with the self-therapy application before it causes other problems requiring professional assistance. This study aimed to determine whether VRT-stressNOmore, an image-based virtual reality with a few realistic University Utara Malaysia environments, can reduce student stress. However, the evidence for image-based virtual reality as a self-therapy is still in the leakage phase. Therefore, the objectives are determining the features that support self-therapy, confirming the features through expert review, designing and developing, and conducting therapeutic test. Implementation of pre-production-post methodology to achieve the goals and objectives. During the week of final exams, 47 healthy undergraduates and 29 healthy postgraduates consented to participate in this study. The T-test result indicates the different values before and after experiencing VRT-stressNOmore, demonstrating the beneficial effect of reducing stress. However, additional research is necessary to confirm the potential and efficacy of VRT-stressNOmore as a self-therapy application for university students.